Methods for measuring egocentric distance perception in visual modality - Dong, Bo; Chen, Airui; Gu, Zhengyin; Sun, Yuan; Zhang, Xiuling; Tian, Xiaoming (Frontiers in Psychology, 2023)
Egocentric distance perception has been widely concerned by researchers in the field of spatial perception due to its significance in daily life. The frame of perception involves the perceived distance from an observer to an object. Over the years, researchers have been searching for an optimal way to measure the perceived distance and their contribution constitutes a critical aspect of the field. This paper summarizes the methodological findings and divides the measurement methods for egocentric distance perception into three categories according to the behavior types. The first is Perceptional Method, including successive equal-appearing intervals of distance judgment measurement, verbal report, and perceptual distance matching task. The second is Directed Action Method, including blind walking, blind-walking gesturing, blindfolded throwing, and blind rope pulling. The last one is Indirect Action Method, including triangulation-by-pointing and triangulation-by-walking. In the meantime, we summarize each method’s procedure, core logic, scope of application, advantages, and disadvantages. In the end, we discuss the future concerns of egocentric distance perception.